Assessing service quality in schools of business: dimensions of service quality in continuing professional education (CPE) - Morales, Miguel (2021)
This paper reports the results of a study on service quality in a business school. We examine the concept of service quality with data collected from 205 executive students. The resulis obtained from applying exploratory factor analysis to our data suggest that the theoretical factor structure consisting offive factors could not be empirically replicated. The empirical factor structure consists of four factors (tangibles, faculty, administration, and reliability-empathy) being reliability-empathy the most important dimension for professional students. Confirmatory factor analysis results provide strong support for the four-dimensional structure of service quality in a business school setting.